Albumin-Modified Melanin-Silica Hybrid Nanoparticles Target Breast Cancer Cells via a SPARC-Dependent Mechanism - Sanità, Gennaro; Armanetti, Paolo; Silvestri, Brigida; Carrese, Barbara; Calì, Gaetano; Pota, Giulio; Pezzella, Alessandro; d’Ischia, Marco; Luciani, Giuseppina; Menichetti, Luca; Lamberti, Annalisa (Frontiers in Bioengineering and Biotechnology, 2020)
Bioconjugation of a recently developed photoacoustic nanoprobe, based on silica-templated eumelanin-silver hybrid nanoparticles (MelaSil_Ag-NPs), with human serum albumin (HSA) is disclosed herein as an efficient and practical strategy to improve photostability and to perform SPARC mediated internalization in breast cancer cells. Modification of NPs with HSA induced a slight viability decrease in breast cancer cells (HS578T) and normal breast cells (MCF10a) when incubated with HSA-NPs up to 100 μg/mL concentration for 72h and a complete suppression of hemotoxicity for long incubation times. Uptake experiments with MelaSil_Ag-HSA NPs indicated very high and selective internalization via SPARC in HS578T (SPARC positive cells) but not in MCF10a (SPARC negative cells), as evaluated by using endocytosis inhibitors. The binding of SPARC to HSA was confirmed by Co-IP and Dot-blot assays. Additional studies were performed to analyze the interaction of MelaSil_Ag-HSA NPs with protein corona. Data showed a dramatic diminution of interacting proteins in HSA conjugated NPs compared to bare NPs. HSA-coated MelaSil_Ag-NPs are thus disclosed as a novel functional nanohybrid for potential photoacoustic imaging applications.